The Effect of Workload on the Performance of Aviation Security Officers at the 2022 Hajj Season Page at Adi Soemarmo Airport - Ade Irma Susanti; Elnia Frisnawati (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Seeing the development of the business world which is currently increasing and competition in the service sector is getting tougher, this has pushed the level of competition in the business sector. Air transportation can also reach remote or remote areas, besides that it can also save travel time compared to other means of transportation such as land and sea. Some of the supervision carried out by Aviation Security officers during the pilgrimage is to check the hajj passengers and their luggage, ensure that the prospective haj passengers enter the special bus for prospective haj pilgrims, place labels on the door and trunk of the bus as a sign that the bus is sterile. of dangerous or prohibited goods, this of course can add to the workload and affect the performance of aviation security officers. This research uses quantitative methods. The data collection process in this study uses primary data. Primary data sources were obtained through interviews and distributing questionnaires which were distributed directly to aviation security officers at Adi Soemarmo airport. The results of this study indicate that based on the partial test results, it can be seen that the calculated t value is 2,338 with a significance level of 0.025. Because t count t table (2.3382000) and significance value 0.05 (0.025 0.05) the decision taken was Ho was rejected and Ha was accepted. Or there is an influence of workload on the performance of aviation security officers at the 2022 Hajj page season at Adi Soemarmo airport. Shows that there is a relationship of 0.216, which means that 21.6% and 79.4% are influenced by other factors or variables